Cyberbullying and Child Protection in Cyberspace: Legal Perspectives and Practical Solutions - Prajaya, Fannzy Bayu Askar; Lubis, Muharman (Jurnal Computech & Bisnis (e-journal), 2025)
Cyberbullying has become a significant problem in the digital realm, particularly affecting children who are frequently susceptible to its detrimental consequences.  This phenomenon presents significant hazards to the mental and physical health of victims, while also cultivating a perilous digital environment.  This article aims to provide a comprehensive examination of cyberbullying from a legal perspective, analyzing its diverse impacts on individuals and society as a whole.  It additionally examines efficacious ways for prevention and intervention.  The research employs an interdisciplinary approach, drawing on insights from legislative frameworks, educational methods, and technological advancements to propose comprehensive solutions.  The paper also analyzes real-life situations in Indonesia, including the incidents of "Audrey in Pontianak" and "Luluk Nuril," emphasizing the obstacles encountered and the prospects for protecting minors online.  The essay concludes with practical recommendations, emphasizing the need for collaboration among governmental bodies, community organizations, and individuals to foster a digital environment that prioritizes safety and promotes children's well-being.  This research aims to contribute to the debate on cyberbullying and foster a safer digital future for young people.